Study of the use of zoledronic acid in pediatric patients with osteogenesis imperfecta at the Fernandes Figueira Institute (IFF/Fiocruz) (Research, Society and Development, 2026)
Osteogenesis Imperfecta (OI) is a rare genetic disorder characterized by bone fragility and wide clinical variability. This study aimed to evaluate the use of zoledronic acid in pediatric patients with OI treated at the Fernandes Figueira Institute (IFF/Fiocruz), describing the clinical profile, therapeutic response, and safety. This retrospective study was conducted between April 2024 and August 2025 and was based on the medical record review of 40 patients aged 2 to 18 years. An equal distribution between sexes was observed, with higher frequency of OI types I, IV, and III. Intravenous pamidronate was the most frequently used initial bisphosphonate, followed by oral alendronate as a transition strategy, while zoledronic acid was subsequently incorporated into the therapeutic regimen of all patients. Adverse events were more common with pamidronate (32.5%) than with zoledronic acid (17.5%), including fever, bone pain, headache, and gastrointestinal symptoms. Before zoledronic acid use, all patients had a history of fractures; after its introduction, only 12.5% reported new episodes, demonstrating a marked reduction. Subjective perception of clinical improvement was recorded in 7.5% of patients. NTX (n=3) and DEXA (n=2) results were insufficient for conclusions regarding bone remodeling or mineral density. Despite limitations related to the scarcity of complementary exams, the findings suggest clinical benefit of zoledronic acid, reinforcing its potential to reduce fractures and improve OI management in pediatric patients within the Brazilian public health context.